ANALYSIS OF THE DISTRIBUTION PATTERN OF TUBERCULOSIS (TB) INCIDENCE IN THE WORKING AREA OF MUARA BELITI HEALTH CENTER, MUSI RAWAS DISTRICT, 2025 - Chandra, Pendana; Wahyudi, Arie; Prima Cakra, Muhammad (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
Tuberculosis (TB) impacts not only physical health but also psychological and economic aspects of individuals and their families. In 2020, global TB-related deaths reached 1.3 million, marking the first annual increase since 2005. Indonesia ranks third globally with a high TB burden, with cases increasing from 724,309 in 2022 to 821,200 in 2023. Similar trends are observed in South Sumatra and the Muara Beliti Health Center's working area, with cases rising from 27 in 2022 to 42 in 2024, highlighting the urgent need for effective TB control strategies. This study aims to analyze the spatial patterns of TB risk in Muara Beliti District, Musi Rawas Regency in 2025 using the Analytic Hierarchy Process (AHP) and Inverse Distance Weighting (IDW) spatial interpolation methods. A key contribution is the integration of behavioral and environmental factors with spatial analysis, allowing for more targeted intervention planning. Using Geographic Information Systems (GIS), this analysis provides accurate insights into high-risk areas, enabling efficient mitigation. The descriptive quantitative method used includes patient characteristic data and coordinates, AHP risk variable weighting, and TB risk pattern visualization using IDW. Results indicate that areas with low contour values (0.5–0.5912) represent high TB risk zones, particularly around Air Lesing, Ketuan Jaya, south of Durian Remuk, and Muara Beliti Baru. Areas with higher contour values (0.786–1) are at lower risk, mostly located in agricultural or sparsely populated regions. Risk maps supported by satellite imagery show TB concentrations in residential areas with poor ventilation and sanitation. In conclusion, the combination of AHP and IDW is effective in identifying spatial TB risk patterns and aiding in the design of focused interventions. Adjusting strategies based on local contexts is crucial. Further studies with broader coverage and additional variables are recommended to enhance the validity and effectiveness of TB control efforts.